Mental imagery in volleyball settings: A scoping review - Ribeiro, J.; Dias, C.; Barbosa Filho, V. C.; Cruz, J.; Fonseca, A. (Journal of Imagery Research in Sport and Physical Activity, 2019)
This article presents a scoping review of the published literature on mental imagery in the context of volleyball. Four online databases and one peer-reviewed journals were searched, based on the inclusion criteria. Publication information, procedures and research methods, sample characteristics, sport type and type of mental imagery were analyzed. The selection process found 52 studies, and results showed that from 1987 to 2018 the mental images, along with other psychological skills, have gained popularity in volleyball settings. The examined studies used cross-sectional and experimental approaches, and the analysis was assessed by quantitative data and/ or mental imagery training programs (with relaxation and scripts), mainly focusing on the isolated analysis of the mental imagery construct, and evaluating its use. The studies included both male and female participants, but only 11% were volleyball players. Additionally, the focus was on adolescents and young adult athletes, mostly from high school/ university or international/ elite levels. However, just two studies examined athletes under the age of 16. Considering the present study`s results, limitations, and its implications for practice (e. g. to provide the coach certification programs with specific mental imagery contents), future research directions were highlighted, such as improve mental imagery training programs for children and youth volleyball players.